iPod & iTunes for dummies - Bove, Tony , 1955- (For dummies, 2011)
Presents an introduction to the key features of iPod, iTunes, and the iTunes music store, explaining how to customize one's device by setting preferences, organize a digital jukebox, copy files, burn an audio CD, preview music tracks, and search for and download songs